Labor Market Flexibility and Unemployment : New Empirical Evidence of Static and Dynamic Effects - Bernal-Verdugo, Lorenzo E. (IMF Working Papers; Working Paper ;, 2012)
The aim of this paper is to analyze the relationship between labor market flexibility and unemployment outcomes. Using a panel of 97 countries from 1985 to 2008, the results of the paper suggest that improvements in labor market flexibility have a statistically and significant negative impact on unemployment outcomes (over unemployment, youth unemployment and long-term unemployment). Among the different labor market flexibility indicators analyzed, hiring and firing regulations and hiring costs are found to have the strongest effect.